Understanding the Seasonal Cycle of Antarctic Sea Ice Extent in the Context of Longer‐Term Variability. (4th September 2019) - Eayrs, Clare; Holland, David; Francis, Diana; Wagner, Till; Kumar, Rajesh; Li, Xichen
Abstract: Over the 40‐year satellite record, there has been a slight increasing trend in total annual mean Antarctic sea ice extent of approximately 1.5% per decade that is made up of the sum of significantly larger opposing regional trends. However, record increases in total Antarctic sea ice extent were observed during 2012–2014, followed by record lows (for the satellite era) through 2018. There is still no consensus on the main drivers of these trends, but it is generally believed that the atmosphere plays a significant role and that seasonal time scales and regional scale processes are important. Despite considerable yearly and regional variability, the mean seasonal cycle of growth and melt of Antarctic sea ice is strikingly consistent, with a slow growth but fast melt season. If we are to project trends in Antarctic sea ice and understand changes on longer time scales, we need to understand the mechanisms related to the seasonal cycle separately from those that drive variability. Twice‐yearly changes in the position and intensity of the zonal winds circling Antarctica are thought to drive the system by working with or against the evolving sea ice edge to slow the autumn advance and hasten the spring melt. Open water regions, created by divergence associated with the zonal winds, amplify the spring melt through increased warming of the upper ocean. Climate models fail to accurately reproduce mean Antarctic sea ice extent and overestimate its year‐to‐year variability, but they tend to capture the pattern and timing of the Antarctic seasonal cycle. Plain Language Summary: Antarctic sea ice extent has been observed daily from satellites over the last 40 years. Compared to the Arctic, there has been little overall change in Antarctic sea ice cover over this time. However, the slightly increasing trend masks substantial interannual and regional variability, and recent years have seen record increases (2012–2014) followed by record lows (through 2018). Despite this variability, the pattern of growth and melt of total Antarctic sea ice shows a consistent, asymmetric cycle with slow growth but rapid melt periods. The presence of many individual storms around the continent gives rise to a band of low pressure that circles the continent, and this low‐pressure band marks a boundary between westerlies to the north and easterlies to the south. Twice‐yearly changes in the position and intensity of these zonal winds work with or against the evolving ice edge to slow the autumn advance and hasten the spring retreat. Open water areas created in the spring lead to increased warming of the upper ocean, which also acts to speed up the spring retreat. On the whole, climate models tend to capture the pattern and timing, but not the magnitude, of the Antarctic seasonal cycle. Key Points: Antarctic sea ice has a remarkably consistent, asymmetric annual cycle, despite substantial interannual variability Zonal winds work with or against the evolving position of the ice edge, and ice‐ocean albedo feedback amplifies the sea ice seasonal cycle Climate models tend to capture the pattern and timing of the Antarctic seasonal cycle but not the magnitude